BRASSINOSTEROID-MEDIATED CHANGES IN ROOT-KNOT NEMATODE SUSCEPTIBLE AND RESISTANT TOMATO CULTIVARS - RAVINDERJIT KAUR; PUJA OHRI; RENU BHARDWAJ (International Journal of Pharma and Bio Sciences, 2014)
Plant-parasitic nematodes are one of the major pests, causing damage to almost all cultivated crops throughout the world. Present nematode control measures pose a threat to the environment; therefore, use of natural compounds is being emphasized to control these deterrents. 28-Homobrassinolide (HBl) is one such naturally synthesized compound that is ubiquitously distributed in plant kingdom. In the present investigation, uniformly sized seeds of susceptible (Pusa Ruby) and resistant (PNR-7) tomato cultivars were treated with different concentrations of HBl. After germination, under controlled conditions seedlings were inoculated with infective juveniles of Meloidogyne incognita. Morphological and biochemical parameters (antioxidative enzymes/ antioxidants) were assessed 72h post-nematode inoculation. Results asserted alterations in plant growth as well as in biochemical parameters post nematode penetration. But supplementing the plants with HBl improved the plant growth and ameliorated the activities of defensive enzymes and antioxidants.